Skin CD4+ Memory T Cells Play an Essential Role in Acquired Anti-Tick Immunity through Interleukin-3-Mediated Basophil Recruitment to Tick-Feeding Sites - Ohta, Takuya; Yoshikawa, Soichiro; Tabakawa, Yuya; Yamaji, Kayoko; Ishiwata, Kenji; Shitara, Hiroshi; Taya, Choji; Oh-hora, Masatsugu; Kawano, Yohei; Miyake, Kensuke; Yamanishi, Yoshinori; Yonekawa, Hiromichi; et al. (Frontiers in Immunology, 2017)
Ticks, blood-sucking arthropods, serve as vectors for transmission of infectious diseases including Lyme borreliosis. After tick infestation, several animal species develop resistance to subsequent infestations, reducing the risk of transmission. In a mouse model, basophils reportedly infiltrate tick-feeding sites during the 2nd but not 1st infestation and play a crucial role in the manifestation of acquired tick resistance. However, the mechanism underlying basophil recruitment to the 2nd tick-feeding site remains ill-defined. Here we investigated cells and their products responsible for the basophil recruitment. Little or no basophil infiltration was detected in T cell-deficient mice, and adoptive transfer of CD4+ but not CD8+ T cells reconstituted it. Il3 gene expression was highly upregulated at the 2nd tick-feeding site, and adoptive transfer of IL-3-sufficient but not -deficient CD4+ T cells conferred the basophil infiltration on T cell-deficient mice, indicating the CD4+ T cell-derived IL-3 is essential for the basophil recruitment. Notably, IL-3+ resident CD4+ memory T cells were detected even before the 2nd infestation in previously-uninfested skin distant from the 1st tick-feeding site. Taken together, IL-3 produced locally by skin CD4+ memory T cells appears to play a crucial role in basophil recruitment to the 2nd tick-feeding site.